2019
DOI: 10.1111/bcp.13934
|View full text |Cite
|
Sign up to set email alerts
|

Perpetrator effects of ciclosporin (P‐glycoprotein inhibitor) and its combination with fluconazole (CYP3A inhibitor) on the pharmacokinetics of rivaroxaban in healthy volunteers

Abstract: Aims: Rivaroxaban exposure is considerably increased by drugs that are combined P-glycoprotein (P-gp) and strong cytochrome P450 (CYP) 3A inhibitors (e.g. ketoconazole). The aim of the present study was to investigate the effects of the potent P-gp inhibitor ciclosporin and its combination with the moderate CYP3A inhibitor fluconazole on rivaroxaban pharmacokinetics and on CYP3A activity.Methods: Twelve healthy volunteers received 20 mg rivaroxaban orally alone, in combination with ciclosporin (dose-individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 36 publications
1
22
0
Order By: Relevance
“…6 Area under the concentration–time curve ratios (AUCR) and maximum (peak) concentration ratios ( C max R) of rivaroxaban with and without concomitantly taken drugs. Results of drug–drug interaction trials that have been conducted and published up to January 2020 are depicted [ 62 , 63 , 69 , 74 , 81 83 , 98 , 104 , 118 – 122 ]. A ratio equals 1 if the co-administered drug statistically insignificantly influenced direct oral anticoagulant (DOAC) pharmacokinetics.…”
Section: Basics Of Doac Pharmacokineticsmentioning
confidence: 99%
“…6 Area under the concentration–time curve ratios (AUCR) and maximum (peak) concentration ratios ( C max R) of rivaroxaban with and without concomitantly taken drugs. Results of drug–drug interaction trials that have been conducted and published up to January 2020 are depicted [ 62 , 63 , 69 , 74 , 81 83 , 98 , 104 , 118 – 122 ]. A ratio equals 1 if the co-administered drug statistically insignificantly influenced direct oral anticoagulant (DOAC) pharmacokinetics.…”
Section: Basics Of Doac Pharmacokineticsmentioning
confidence: 99%
“…Thus, patients treated with single modulators of multiple elimination pathways or multiple modulators of single-elimination pathways (CYP3A, P-gp) need extra care, both in daily practice and also in drug labels. 4 After an oral dose of 10 mg rivaroxaban, the metabolite profile in human plasma showed unchanged rivaroxaban concentration. Neither major nor active circulating metabolites were present in the main compound.…”
mentioning
confidence: 99%
“…The addition of fluconazole increased the average exposure of rivaroxaban further. Thus, patients treated with single modulators of multiple elimination pathways or multiple modulators of single‐elimination pathways (CYP3A, P‐gp) need extra care, both in daily practice and also in drug labels …”
mentioning
confidence: 99%
“…The study of effect of a potent P-gp inhibitor cyclosporin and its combination with a moderate CYP3A inhibitor fluconazole on pharmacokinetics of rivaroxaban and CYP3A activity (compared with baseline) showed that cyclosporine increased average exposure of rivaroxaban by 47%, maximum concentration of CYP3A4 and decreased by 34%, and cyclosporine in combination with fluconazole increased the average exposure of rivaroxaban by 86% and maximum concentration by 115%. This effect was significantly stronger than that observed in control group that received rivaroxaban with fluconazole alone [57].…”
Section: Rivaroxabanmentioning
confidence: 61%